Intense pulsed light (IPL) as adjuvant therapy for acne vulgaris: A case series - Oentari, Widyaningsih; Sutrisno, Angie Regina; Jusuf, Nelva Karmila; Nasution, Khairina (UI Scholars Hub, 2021)
Background: Acne vulgaris is a chronic inflammatory disease of the pilosebaceous follicle with polymorphic clinical manifestation typically found on facial, neck and/or back area. The pathogenesis is complex and multifactorial. Management of acne vulgaris is determined based on its severity. Adjuvant therapies, such as intense pulsed light (IPL), have been described in accelerating the healing process during treatment. Case Illustration: We report two cases regarding the usage of IPL as adjuvant therapy in acne vulgaris. Both patients were diagnosed with moderate acne vulgaris. The first patient was given topical adapalene 0.1% gel every night and sunscreen in the morning, and the other patient was given clindamycin gel applied twice a day, benzoyl peroxide 2.5% cream applied once a day at night, and sunscreen in the morning. Both patients were treated using IPL as their adjuvant therapy every three weeks, with a total of 2 IPL sessions in 2 months. Evaluation using clinical and ultraviolet-induced red fluorescence (UVRF) examination showed gradual improvement. Discussion: IPL as an adjuvant therapy of acne vulgaris has been thought to interfere with the function of the sebaceous glands by its direct phototoxic effects and thermal damage. It also has bactericidal effects on C. acnes through the formation of free radicals. The combination of topical treatment and IPL yielded clinical improvements in both patients.Conclusion: IPL may be beneficial as adjuvant therapy in acne vulgaris in this case series.